Free energy of 3D Ising-like system near the phase transition point - Kozlovskii, M.P. (Condensed Matter Physics, 2009)
A generalized representation for the scaling form of free energy of the system near the phase transition point
is proposed. Explicit expressions for coefficients as functions of the reduced temperature and external field in
the case of T > Tc are obtained at the microscopic level. Запропонована узагальнена форма запису скейлiнгової форми вiльної енергiї системи поблизу точки фазового переходу. На мiкроскопiчному рiвнi строгостi отриманi явнi вирази для коефiцiєнтiв як функцiй вiдносної температури та зовнiшнього поля для випадку T > Tc.